Investigation of plasma transferred arc dynamic effects in wire + arc additive manufacturing - Bridgeman, Philippe James (Cranfield University, 2021)
This investigation focuses on the effect of plasma transferred arc (PTA) parameters and torch geometry on arc pressure to characterise the soft plasma process and the avoidance of keyhole defect formation. A measured arc pressure comparison with gas tungsten arc (GTA) was also undertaken. The objective being to minimise arc pressure, reducing any depression of the melt-pool and thereby its effects on bead geometry. Both are essential for the wire + arc additive manufacture (WAAM) process. The research approach includes experimental measurement of arc pressure for combinations of torch nozzle and electrode geometries and process variables to determine the process sensitivities and their effect on the arc pressure, and to determine reduction methods. A novel concept of an arc interaction time, relating to gas conditioning, arc characteristics and the strength of the arc pressure, is proposed. A relationship between arc voltage and peak arc pressure is identified and proposed as a potential method of real-time pressure monitoring during WAAM operations. An empirical statistic process model was developed, which relates arc pressure to process conditions and torch design, allowing the selection of process variables while maintaining a minimum arc pressure in PTA WAAM, thus enabling higher currents and larger deposition rates while minimising keyhole defect risk. Arc pressure keyhole defect transition thresholds are identified for both stainless-steel and titanium. Arc pressure is determined as the predominant factor for initiating sharp keyhole defect transitions for a set of thermal conditions – a balance between thermal melt-pool fluid flow and arc pressure-induced hole size. A study of PTA electrodes was additionally undertaken to reduce arc pressure, improve arc starting, investigate wear and increase the longevity of electrodes and tip shape retention to optimise WAAM operations.
Ding, Jialuo - Associate Supervisor
Keywords: Arc Pressure; Keyhole Defects; Plasma Transferred Arc (PTA); Experimental Measurement; Additive Manufacture; Wire + Arc Additive Manufacture (WAAM); Empirical Process Model; Electrode Wear